1989
DOI: 10.1111/j.1439-0418.1989.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the exposition and temperature of nests of Thaumetopoea pityocampa (Den. & Schiff.) (Lep., Thaumetopoeidae) in Greece

Abstract: Studies on nests of the pine processionary caterpillar were carried out in different parts of Greece in the years 1985 to 1988. Most of the nests could be found at the southeast, south and southwest of pine trees. Deviations in the distribution could be due to the slope of forests and a high population pressure. Registering of temperature data verified that the inner temperature of the caterpillar nests could rise quite high. Such a warming is clearly dependent on the intensity of the insolation and the thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 2 publications
(4 reference statements)
2
30
0
Order By: Relevance
“…The zones dominated by this pine species have a mild climate in winter, conducive to PPM development irrespectively of NAO phases. Pines in these areas need to be resistant to PPM because its incidence is chronic, and predators and parasitoids probably have more diverse and developed populations than in high-mountain sites, and it is known that stone pine is the species least susceptible to the PPM (Démolin 1969b;Avtzis 1986;Breuer et al 1989;Devkota and Schmidt 1990;Tiberi et al 1999). As a result, the defoliation dynamics in the woodland stands dominated by stone pine differ sharply from those of more palatable pines (black or Scots pine, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The zones dominated by this pine species have a mild climate in winter, conducive to PPM development irrespectively of NAO phases. Pines in these areas need to be resistant to PPM because its incidence is chronic, and predators and parasitoids probably have more diverse and developed populations than in high-mountain sites, and it is known that stone pine is the species least susceptible to the PPM (Démolin 1969b;Avtzis 1986;Breuer et al 1989;Devkota and Schmidt 1990;Tiberi et al 1999). As a result, the defoliation dynamics in the woodland stands dominated by stone pine differ sharply from those of more palatable pines (black or Scots pine, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is a key factor determining the outbreak capacity of PPM, as low winter temperatures heavily determine the larval survival of this insect (e.g. Breuer et al 1989;Battisti et al 2005;Buffo et al 2007). Several studies have found, as a consequence of the general rise in temperatures, a progression in latitude and/or altitude with respect to the previous distribution of the pest, as well as an increase in outbreak severity (Hódar et al 2003;Battisti et al 2005Battisti et al , 2006Robinet et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Different species of the pines serve as the host plants to these polyphagous voracious feeders. In Kalogria (Greece), P. halepensis is overwhelmingly preferred to P. pinea ( BREUER et al 1989) where both stands occur together. In the eastern Mediterranean forests, the three close relatives of pines P. eldarica, P. brutia and P. halepensis are attacked in decreasing magnitude by T.…”
Section: Introductionmentioning
confidence: 99%
“…As tent temperatures are always 0.5–9°C higher than air temperatures (Breuer et al. ), we assume that, in our study site, tent temperatures were above 6°C when the preceding day's maximum air temperatures were close to 0°C Secondly, we included the average minimum daily temperatures, which had been suggested by Buffo et al. () as a suitable index for PPM winter feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, we examined the number of days with a minimum temperature above 0°C, which is the lowest PPM feeding limit (Huchon and D emolin 1970) with temperatures inside the tent reaching at least 6°C the preceding day (Battisti et al 2005). As tent temperatures are always 0.5-9°C higher than air temperatures (Breuer et al 1989), we assume that, in our study site, tent temperatures were above 6°C when the preceding day's maximum air temperatures were close to 0°C Secondly, we included the average minimum daily temperatures, which had been suggested by Buffo et al (2007) as a suitable index for PPM winter feeding. In addition, another CIV, the average minimum temperatures for the October-March period, indicated by Robinet et al (2007) as the best predictor of the number of PPM feeding days, were also evaluated.…”
Section: Climate Effects On Ppm Fecunditymentioning
confidence: 99%